SPEECH DEVELOPMENT OF YOUNG SCHOOL STUDENTS (Academia Science Repository, 2023)
This article provides information on speech development of young children. The role of the family and preschool educational institution in the development of the speech of young children is incomparable. It is an important process to enrich speech, to develop necessary skills and competencies.